Prevalence of frailty in patients with non-cirrhotic non-alcoholic fatty liver disease. Issue 1 (6th May 2022) - Naimimohasses, Sara; O'Gorman, Philip; McCormick, Emma; Ferguson, Damien; Monaghan, Ann; McGrath, Marie; Robinson, Mark W; Gormley, John; Norris, Suzanne
Abstract : Objective: End-stage chronic liver disease is associated with accelerated ageing and increased frailty. Frailty measures have provided clinical utility in identifying patients at increased risk of poor health outcomes, including those awaiting liver transplantation. However, there is limited data on the prevalence and severity of frailty in patients with non-cirrhotic non-alcoholic fatty liver disease (NAFLD). The aim of this study was to evaluate the prevalence of frailty and prefrailty in patients with non-cirrhotic NAFLD and correlate with severity of liver disease. Design: A cross-sectional analysis of functional and laboratory frailty assessments, including the Fried frailty index (FFI), a self-reported frailty index (SRFI) and a lab-based frailty index (FI-LAB), was performed in a cohort of 109 patients with NAFLD, and results compared with fibrosis staging based on transient elastography. Results: Patients with NAFLD had a high prevalence of prefrailty and frailty, with a median SRFI score of 0.18 (IQR: 0.18), FFI of 1 (IQR: 1) and FI-LAB of 0.18 (IQR: 0.12). Using the SRFI, 45% of F0/F1 patients were classified as prefrail and 20% were classified as frail, while in F2/F3 patients this increased to 36% and 41%, respectively. SRFI, 30 s sit-to-stand and FI-LAB scores increased with increasing liver fibrosis stages (p=0.001, 0.006 and <0.001, respectively). On multivariate linear regression, female gender was identified as a significant predictor of elevated frailty scores. Conclusion: This study identifies a high prevalence of frailty in individuals with non-cirrhotic NAFLD. Addressing frailty through early rehabilitation interventions may reduce overall morbidity and mortality in this population.